Graphene perfect absorber with loss adaptive Q-factor control function enabled by quasi-bound states in the continuum - Lee, Sangjun; Song, Joohyung; Kim, Sangin (Scientific Reports, 2021)
Numerous device structures have been proposed for perfect absorption in monolayer graphene under single-sided illumination, all of which requires the critical coupling condition, i.e., the balance between the loss of graphene and the leakage rate of the device. However, due to the difficulty of the precise control of the quality of synthesized graphene and unwanted doping in graphene transferred to the substrate, the loss of graphene is rather unpredictable, so that the perfect absorption is quite difficult to achieve in practice. To solve this problem, we designed a novel perfect absorber structure with a loss adaptive leakage rate control function enabled by the quasi-bound states in the continuum (BIC) and numerically demonstrated its performance. Our designed device is based on a slab-waveguide grating supporting both the quasi-BIC and the guided-mode resonance (GMR); the quasi-BIC with an adjustable leakage rate controlled by an incident angle is responsible for absorption, while the GMR works as an internal mirror. Since the proposed device scheme can have an arbitrarily small leakage rate, it can be used to implement a perfect absorber for any kind of ultrathin absorbing media. Due to the simple structure avoiding an external reflector, the device is easy to fabricate.